Pemasangan Instalasi Listrik Penerangan Untuk Masyarakat Binaan Disnaker di Pemkot Malang - Sukamdi; Anang Dasa Novfowan; Mochammad Mieftah; Rachmat Sutjipto; Dhimas Dhesah Kharisma (Politeknik Negeri Malang, 2020)
This study discusses the installation of lighting electrical installations that are appropriate and safe for the community assisted by the Manpower Office in Malang City Government. The existence of this research is expected to provide additional skills in installing lighting installations, to be used in working to install lighting installations that are correct and safe and in accordance with standards, so as to minimize work hazards or accidents due to errors due to installation and use. This research activity was carried out in the AK Building of Malang State Polytechnic, Jalan Soekarno Hatta Malang by Malang State Polytechnic. The research activity for lighting electrical installations was carried out using a direct practice method. These activities are the introduction of standard electrical installation equipment according to PUIL; Introduction of lighting equipment components such as lamps, switches, contact boxes; and Installation of fittings, contact boxes, pipes, cables, switches. From the results of the research which was carried out for several days, the results obtained were knowing the practical theory of lighting installation; know the use of PPE properly; know the components of the lighting installation; know the electric measuring instruments; knowing how to install lighting installation components correctly and safely; know what things are done before the object is connected to a power source; and can take measurements when the object has been connected to a power source.